Performance Appraisal in Pharmacy Department Sultan Agung Islamic Hospital by Balanced Scorecard Approach on Internal Business Perspectives - Sulistyaningrum, Indriyati Hadi; Wirastuti, Ken; Santoso, Arifin; Afif M., Muhammad Mujib (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2016)
Background: Performance appraisal using Balanced Scorecard on internal business process perspective offers a comprehensive solution for performance appraisal in public organization especially in a hospital. Objective: to study the performance of pharmacy department in Sultan Agung Islamic Hospital using Balanced Scorecard from internal business perspective. Methods: Object of the study is the Sultan Agung Islamic Hospital installation of pharmacy. This research is a descriptive observational study. Data were obtained prospectively and then categorized and grouped as quantitative and qualitative data. Qualitative data were gathered from in depth interview with head of pharmacy department Sultan Agung Islamic Hospital. Quantitative data were gathered from direct observation on drugs prescription surveys.Result : Performance perspective on internal business process include: a. Level of availability of drugs in pharmacy department Sultan Agung Islamic Hospital is good with average 98%, b. Level of outpatients admittance in installation of pharmacy Sultan Agung Islamic hospital indicated the average of 66%, it means that installation of pharmacy have lost customers for outpatients as much as 34%.Conclusion: Performance in pharmacy installation of Sultan Agung Islamic Hospital is not in a good criteria, therefore improvement is needed.